A sphere of resonance for networked learning in the 'non-places' of our universities. (12th June 2015) - Hayes, Sarah
The logic of 'time' in modern capitalist society appears to be a fixed concept. Time dictates human activity with a regularity, which as long ago as 1944, George Woodcock referred to as The Tyranny of the Clock. Seventy years on, Hartmut Rosa suggests humans no longer maintain speed to achieve something new, but simply to preserve the status quo, in a 'social acceleration' that is lethal to democracy. Political engagement takes time we no longer have, as we rush between our virtual spaces and 'non-places' of higher education. I suggest it is time to confront the conspirators that, in partnership with the clock, accelerate our social engagements with technology in the context of learning. Through Critical Discourse Analysis I reveal an alarming situation if we do not. With reference to Bauman's Liquid Modernity, I observe a 'lightness' in policy texts where humans have been 'liquified' Separating people from their own labour with technology in policy maintains the flow of speed a neoliberal economy demands. I suggest a new 'solidity' of human presence is required as we write about networked learning. 'Writing ourselves back in' requires a commitment to 'be there' in policy and provide arguments that decelerate the tyranny of time. I am, though, ever-mindful that social acceleration is also of our own making, and there is every possibility that we actually enjoy it.